Review of Smart Services for Tinnitus Self-Help, Diagnostics and Treatments - Kalle, Sven; Schlee, Winfried; Pryss, Rüdiger C.; Probst, Thomas; Reichert, Manfred; Langguth, Berthold; Spiliopoulou, Myra (Frontiers in Neuroscience, 2018)
In the recent years, there has been an increased interest in the potential of internet-based and smartphone-based technologies for the support of tinnitus patients. A broad spectrum of relevant approaches, some in the form of studies, others in the form of market products, have been mentioned in the literature. They include auditory treatments, internet-based Cognitive Behavioral Therapy (iCBT), serious games and questionnaires for tinnitus monitoring. Goal of this study is to highlight the role of existing technologies in the tinnitus field, distinguishing among contributions with respect to treatment, diagnostics and self-help. We elaborate on the potential and the challenges of such solutions and identify constraints associated to their deployement, such as the demand for familiarity with internet-based services and the need to re-design interactive services so that they fit on the small surface of a smartwatch.